Tidal mitigation of offshore wind wake effects in coastal seas - Christiansen, Nils; Daewel, Ute; Schrum, Corinna (Frontiers in Marine Science, 2022)
With increasing offshore wind development, more and more marine environments are confronted with the effects of atmospheric wind farm wakes on hydrodynamic processes. Recent studies have highlighted the impact of the wind wakes on ocean circulation and stratification. In this context, however, previous studies indicated that wake effects appear to be attenuated in areas strongly determined by tidal energy. In this study, we therefore determine the role of tides in wake-induced hydrodynamic perturbations and assess the importance of the local hydrodynamic conditions on the magnitude of the emerging wake effects on hydrodynamics. By using an existing high-resolution model setup for the southern North Sea, we performed different scenario simulations to identify the tidal impact. The results show the impact of the alignment between wind and ocean currents in relation to the hydrodynamic changes that occur. In this regard, tidal currents can deflect emerging changes in horizontal surface currents and even mitigate the mean changes in horizontal flow due to periodic perturbations of wake signals. We identified that, particularly in shallower waters, tidal stirring influences how wind wake effects translate to changes in vertical transport and density stratification. In this context, tidal mixing fronts can serve as a natural indicator of the expected magnitude of stratification changes due to atmospheric wakes. Ultimately, tide-related hydrodynamic features, like periodic currents and mixing fronts, influence the development of wake effects in the coastal ocean. Our results provide important insights into the role of hydrodynamic conditions in the impact of atmospheric wake effects, which are essential for assessing the consequences of offshore wind farms in different marine environments.